Heavy metal accumulation in commercially important fishes of south west Malaysian coast - Yunus, Kamaruzzaman; Zabri, Rina Sharlinda; John, Akbar; Khan Chowdhury, Ahmed Jalal (Academic Journals Inc., USA, 2011)

(untitled)
Now-a-days, bioaccumulation of toxic metals in aquatic animals causes serious threats to the human health when they are consumed. Thus the detection of toxic elemental concentration in aquatic flora and fauna has attracted various researches to determine their toxic levels in organism’s edible parts. Upon considering this issue, the accumulation of some heavy metals such as Mercury (Hg), Arsenic (As), Lead (Pb) and Zinc (Zn) in Muscle and gill tissues were determined in commercially important fishes. Five species (Nemipterus japonicas, Chirocentrus dorab, Lutjanus sebae, Otolithes ruber and Pampus argenteus) were collected from south west coast of Malaysia, covering 3 states (Johor, Melaka and Negeri Sembilan). Metal concentration was determined using Inductively Coupled Plasma Mass Spectrometer (ICP-MS). In general, higher metal accumulation was detected in gill tissues than the muscle tissue of selected fishes while Hg concentration was higher in muscle tissues except in Pampus argenteus. Similar observation was noted in As and Pb accumulation in N. japonicus and L. sebae, respectively. Hg and As concentration was higher in P. argenteus muscle and gill tissues on the other hand higher Pb and Zn level was noted in Muscle tissues L. sebae. Higher concentration of Pb and Zn were detected in gill tissues of L. sebae and O. ruber, respectively. There was no species specific differences in metal accumulation were noted (p<0.05). It was also observed that essential metal level in fish samples were greater than non-essential toxic metals. The metal concentrations found in this study were lower than the national and international standard maximum permissible limits for human consumption. Therefore, no public health problem would be raised in the consumption of these fishes. .